Pengaruh Kualitas E-Layanan Mobile Banking terhadap Kepuasan Nasabah dalam Menciptakan Loyalitas dan Word of Mouth - William Kennedy; Patrick Kevin Aritonang (Economic Reviews Journal, 2025)
The digital era has brought significant changes in the banking sector, driven by advances in information technology and widespread internet penetration. These technological advances also pose competitive challenges that require banks to continuously innovate and improve service quality. One such innovation is mobile banking. The implementation of digital technology such as mobile banking is crucial for banks to maintain business sustainability, maintain relevance, and increase customer satisfaction and loyalty in this digital era. The purpose of this study is to analyze the effect of mobile banking e-service quality on customer satisfaction and the impact of customer satisfaction on loyalty and word of mouth (WOM). This study uses a quantitative approach with a survey method by distributing questionnaires to 148 mobile banking users aged 17-44 years and having used mobile banking for at least 3 months in the Jakarta area. This study uses a Structural Equation Model (SEM) data analysis method based on Partial Least Squares (PLS). The results show that the quality of mobile banking e-services consisting of reliability, privacy/security, web design, and customer service has a significant effect on customer satisfaction. Meanwhile, customer satisfaction in using mobile banking e-services has a significant effect on loyalty and WOM. These findings indicate that good quality mobile banking e-services can increase customer satisfaction and have an impact on creating loyalty and positive WOM.